Vestibular Schwannoma: Presenting Symptoms in A Series Of 106 Patients - Ergashev, Jamol; Santos, Sofia; Soto, Andrés; Amonov, Shavkat (International Journal of Psychosocial Rehabilitation, 2020)
The authors were a retrospective study of 106 patients with vestibular schwannoma (VS) which was conducted in the population of Galicia, who visited to the University Hospital Santiago de Compostela from February 21, 1992 to March 3, 2014. In this study, we included only VS cases, and most of them were diagnosed by MRI with enhanced gadolinium. As exclusion criteria, we used tumors separately from VS or cases of CPA tumors of unknown origin. According to the authors, the clinical manifestations of the sun vary greatly and include unilateral high-frequency sensorineural hearing loss, tinnitus, imbalance, pressure in the ear, earache, sometimes dizziness, instability, etc. The deterioration of clinical signs often associated with a tumor growth. The most common symptom at the time of diagnosis is hearing loss. Type of hearing loss is a neurosensory high frequency hearing loss with an oblique audiometric configuration.